INVESTIGATING THE EFFECTS OF OMEGA-3 FATTY ACIDS ON COGNITIVE FUNCTION IN INDIVIDUALS WITH DYSLEXIA: A SYSTEMATIC REVIEW OF EXISTING RESEARCH - Sheik Nashitah Hussain (International Educational Journal of Science and Engineering, 2024)
The objective of this paper is to review the possible effects of omega-3 fatty acids, specifically docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), on cognitive ability in individuals with dyslexia. Omega-3 fatty acids have been demonstrated to decrease oxidative stress and inflammation within the brain. This is especially important in dyslexia, as elevated levels of oxidative stress markers have been identified. Omega-3s may enhance brain function by protecting neurons from degradation by reducing oxidative damage. The EPA also helps protect the brain by reducing inflammation, which can negatively impact cognitive abilities and learning ability. Dyslexia is a neurodevelopmental disorder characterized primarily by error patterns in reading, but it also impacts memory, attention, and other functions. Its roots lie in deficits in phonological processing and working memory, often leading to the underactivation of particular brain regions such as the left temporoparietal cortex. While traditional interventions rely on educational strategies, emerging research suggests that omega-3 fatty acids, known for their crucial role in brain development and function, may provide cognitive benefits that complement existing treatments.